What Are the Key Issues in the Development of Effective Poverty Alleviation Policies and Their Implementation in China’s South West Regions? - Feng, Haying; Squires, Victor (Advances in Social Sciences Research Journal, 2022)
In this paper we examine, against the background of the government’s poverty alleviation agenda, issues that influence (negatively or positively) the widespread adoption of entrepreneurial initiatives by farmers, foresters, fisherman and others that could contribute to defeating poverty. We summarize trends in poverty levels, the inequality ‘gap’ and touch on government-led initiatives. These include inputs to modernize farm equipment, to provide start-up capital to returning entrepreneurial migrant workers and to foster digital marketing of locally produced (but in demand) commodities.